Pengaruh Kepemimpinan Dan Lingkungan Kerja Terhadap Kinerja Karyawan CV Nabilah Di Bekasi: The Influence of Leadership and Work Environment on the Performance of CV Nabilah Employees in Bekasi - Fahrani Juhana; Suhardoyo Suhardoyo; Heri Kuswara (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
Abstract - This study aims to determine the effect of leadership and work environment on employee performance at CV Nabilah in Bekasi. The research used a quantitative approach with a survey method. The sample consisted of 50 employees selected through a saturated sampling technique. Data were collected using a Likert-scale questionnaire and then analyzed with SPSS version 26. The validity test results confirmed that all items were valid, while the reliability test showed Cronbach’s Alpha values above 0.60, indicating that the instrument was reliable. The t-test showed that leadership significantly affected employee performance (t = 3.531 > t-table = 1.985), as did the work environment (t = 2.145 > t-table = 1.985). The F-test showed an F value of 26.029 > F-table = 3.19, meaning there is a simultaneous significant influence. The Adjusted R Square value of 0.503 indicates that 50.3% of employee performance is influenced by leadership and the work environment, while the remaining 49.7% is influenced by other factors beyond this study.